2014
DOI: 10.1016/j.jsat.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Emerging adult age status predicts poor buprenorphine treatment retention

Abstract: Emerging adults (18–25 years old) are often poorly retained in substance use disorder treatment. Office-based buprenorphine often enhances treatment retention among people with opioid dependence. In this study, we examined the records of a collaborative care buprenorphine treatment program to compare the treatment retention rates of emerging adults versus older adults. Subjects were 294 adults, 71 (24%) aged 18–25, followed in treatment with buprenorphine, nurse care management, and an intensive outpatient pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 64 publications
9
81
2
Order By: Relevance
“…First, complete abstinence rates for emerging adults with opioid dependence were substantially higher at 12 month follow-up (29%) than was expected given results from a prior study of emerging adults with opioid dependence enrolled in outpatient B/N maintenance treatment, which had only 17% 12-month retention (Schuman-Olivier et al, 2014). Even though self-reported “abstinence” and treatment “retention” can differ, within opioid maintenance treatment programs, non-retention is strongly associated with dropout and relapse to illicit opioid use (Schuman-Olivier et al, 2014; Zhang et al, 2003). Notably, 6-month complete abstinence rates after this residential treatment (42.5%) were similar to 6-month retention rates in buprenorphine maintenance treatment (38%; Schuman-Olivier et al, 2014).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…First, complete abstinence rates for emerging adults with opioid dependence were substantially higher at 12 month follow-up (29%) than was expected given results from a prior study of emerging adults with opioid dependence enrolled in outpatient B/N maintenance treatment, which had only 17% 12-month retention (Schuman-Olivier et al, 2014). Even though self-reported “abstinence” and treatment “retention” can differ, within opioid maintenance treatment programs, non-retention is strongly associated with dropout and relapse to illicit opioid use (Schuman-Olivier et al, 2014; Zhang et al, 2003). Notably, 6-month complete abstinence rates after this residential treatment (42.5%) were similar to 6-month retention rates in buprenorphine maintenance treatment (38%; Schuman-Olivier et al, 2014).…”
Section: Discussionmentioning
confidence: 83%
“…In order to compare with rates reported in a prior study of emerging adults with opioid dependence receiving buprenorphine maintenance (Schuman-Olivier et al, 2014), we also used chi-squared tests to examine between-group differences in complete abstinence during follow-ups measured at 6-month as past 90 days abstinence, and at 12-month as past 180 days complete abstinence. In order to be conservative, missing a follow-up assessment was assumed to represent non-abstinent/relapsed status.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has shown that emerging adults may have worse psychosocial and SUD treatment outcomes than older adults, including a lower likelihood of completing treatment (McHugh et al, 2013;Mertens & Weisner, 2000;SchumanOlivier et al, 2014;Vuoristo-Myllys et al, 2013) and greater substance use or less abstinence during or following treatment exposure (Dennis et al, 2009;Hoeppner et al, 2014;Schuman-Olivier et al, 2014;Sinha et al, 2003).…”
Section: Need For Specific Clinical Focus On Emerging Adultsmentioning
confidence: 99%